2023
DOI: 10.1155/2023/1621873
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum 25-Hydroxyvitamin D and Abdominal Aortic Calcification: A Large Cross-Sectional Study

Abstract: In the American population, the relationship between the standardized serum 25-hydroxyvitamin D (25(OH)D) concentration and the risk of abdominal aortic calcification (AAC) is unclear. The purpose of our study was to investigate the relationship between serum 25(OH)D concentration and AAC risk. Participants from the National Health and Nutrition Examination Survey (NHANES) between 2013 and 2014 were analyzed cross sectionally. An analysis of the relationship between serum 25(OH)D concentration and incident AAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Nevertheless, a study involving older African American women revealed no significant relationship between abdominal aorta and serum 25-OH-D levels [ 39 ]. A large cross-sectional study found a U-shaped relationship between serum 25(OH)D concentration and the risk of abdominal aortic calcifcation(AAC) and severe AAC [ 40 ]. Although it has been established that the combination of cinacalcet and low-dose vitamin D can alleviate CAC [ 16 ], another prospective study involving HD patients with SHPT [ 41 ] found no significant difference between the effect of cinacalcet combined with standard therapy versus standard therapy alone on vascular calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a study involving older African American women revealed no significant relationship between abdominal aorta and serum 25-OH-D levels [ 39 ]. A large cross-sectional study found a U-shaped relationship between serum 25(OH)D concentration and the risk of abdominal aortic calcifcation(AAC) and severe AAC [ 40 ]. Although it has been established that the combination of cinacalcet and low-dose vitamin D can alleviate CAC [ 16 ], another prospective study involving HD patients with SHPT [ 41 ] found no significant difference between the effect of cinacalcet combined with standard therapy versus standard therapy alone on vascular calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a study involving older African American women revealed no significant relationship between abdominal aorta and serum 25-OH-D levels 37 . A large cross-sectional study found a U-shaped relationship between serum 25(OH)D concentration and the risk of abdominal aortic calcifcation(AAC) and severe AAC 38 . Although it has been established that the combination of cinacalcet and low-dose vitamin D can alleviate CAC 16 , another prospective study involving HD patients with SHPT 39 found no significant difference between the effect of cinacalcet combined with standard therapy versus standard therapy alone on vascular calcification.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this this version posted December 17, 2023. ; https://doi.org/10.1101/2023.12.16.23300066 doi: medRxiv preprint 2 0 concentration and the risk of abdominal aortic calcifcation(AAC) and severe AAC 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who had smoked less than 100 cigarettes in their lifetime, do not smoke at present, smoked more than 100 cigarettes in their lifetime and smoked some days or every day were defined as non-smokers, former smokers, and current smokers, respectively. There were five categories of drinkers: non-drinkers were defined as had < 12 drinks in lifetime; former drinkers were defined as had ≥ 12 drinks in 1 year and did not drink last year, or did not drink last year but drank ≥ 12 drinks in lifetime; current heavy alcohol consumption was defined as ≥ 3 drinks per day for females, or binge drinking (≥ 4 drinks on the same occasion for females) on five or more days per month; current moderate alcohol consumption was defined as ≥ 2 drinks per day for females, or binge drinking ≥ 2 days per month; and current mild alcohol use was defined as not meeting the above criteria [ 20 ]. After resting quietly in a sitting position for 5 min and determining the maximum inflation level, three consecutive blood pressure readings are obtained.…”
Section: Methodsmentioning
confidence: 99%